IMMUNE RESPONSES IN VITRO : I. CELLULAR REQUIREMENTS FOR THE IMMUNE RESPONSE BY NONPRIMED AND PRIMED SPLEEN CELLS IN VITRO - Pierce, Carl W. (The Rockefeller University Press, 1969)
A cell suspension culture system combined with a procedure which separates most macrophages from lymphoid cells was used to investigate some of the cellular requirements for direct and indirect plaque-forming cell responses by nonprimed and primed mouse spleen cells in vitro. The plaque-forming cell response to heterologous erythrocytes in cultures of nonprimed spleen cells required both macrophages and lymphoid cells for its development. A significant indirect plaque-forming cell response did not develop in cultures of nonprimed spleen cells. In contrast, cultures of separated or macrophage-poor lymphoid cells from primed mice exhibited increasing responses relative to the response of unseparated spleen cells as the interval after priming increased. The cultures of separated lymphoid cells were not entirely free of phagocytic cells. Despite some evidence which suggests that these phagocytic cells had little function in the response, one cannot ascertain whether the lymphoid cells were responding directly to a second contact with antigen or whether the few contaminating phagocytic cells were performing a function essential to the response by the lymphoid cells. Physiologically different populations of cells appear to develop after priming and are able to respond in vitro in a macrophage-poor culture. Some of the properties of these populations suggest that they are "memory cell" pools containing precursors of direct and indirect plaque-forming cells highly susceptible to a second antigenic stimulus.